Cooking with legends. Ming Tsai & Rick Bayless [videorecording (DVD)] (PBS, 2026)
Cooking with Legends: Ming Tsai & Rick Bayless refers to multiple guest appearances by renowned chef Rick Bayless on Ming Tsai's PBS cooking show, Simply Ming, highlighting East-meets-West cuisine, especially Mexican flavors with Asian twists, featuring dishes like Mexican adobo tacos with Moo Shu wraps, swordfish, and Okonomiyaki, showcasing their collaborative spirit and culinary expertise. These episodes blend their distinct styles, creating unique fusion dishes and exploring themes like comfort food and seasonal ingredients.